River secrets - Hale, Shannon (Hale, Shannon. Books of Bayern., 2017)
Young Razo travels from Bayern to Tira at war's end as part of a diplomatic corps, but mysterious events in the Tiran capital fuel simmering suspicions and anger, and Razo must spy out who is responsible before it is too late and he becomes trapped in an enemy land.